Trend-cycle decomposition of output and euro area inflation forecasts: a real-time approach based on model combination - Pierre Guérin; Laurent Maurin; Matthias Mohr (European Central Bank (ECB), 2011)
The paper focuses on the estimation of the euro area output gap. We construct model-averaged measures of the output gap in order to cope with both model uncertainty and parameter instability that are inherent to trend-cycle decomposition models of GDP. We first estimate nine models of trend-cycle decomposition of euro area GDP, both univariate and multivariate, some of them allowing for changes in the slope of trend GDP and/or its error variance using Markov-switching specifications, or including a Phillips curve. We then pool the estimates using three weighting schemes. We compute both ex-post and real-time estimates to check the stability of the estimates to GDP revisions. We finally run a forecasting experiment to evaluate the predictive power of the output gap for inflation in the euro area. We find evidence of changes in trend growth around the recessions. We also find support for model averaging techniques in order to improve the reliability of the potential output estimates in real time. Our measures help forecasting inflation over most of our evaluation sample (2001-2010) but fail dramatically over the last recession.
Keywords: C53; E32; E37; 330; auxiliary information; inflation forecast; Kalman filter; Markov-switching; model averaging; Phillips curve; real-time analysis; trend-cycle decomposition; unobserved components model